GAP/METAL SCHOTTKY DİYOTUNUN HAZIRLANMASI VE ELEKTRONİK ÖZELLİKLERİNİN İNCELENMESİ - EROL, SEVİL (Fırat Üniveristesi, 2010)
Bu çalışmada LEC tekniği ile hazırlanan Galyum Fosfat (GaP) ince filminin optik ve elektriksel özellikleri incelendi. Numunenin optiksel özellikleri soğurma ve transmitans ölçümleri elde edilerek araştırıldı. Bu ölçümlerden GaP ince filminin yasak enerji aralığı 2,24 eV olarak elde edildi. Kırılma indisi - dalga boyu değişimi ve titreşim enerjisi incelendi. Daha sonra yarıiletken tabakanın bir yüzü Alüminyum (Al) kaplandı ve omik kontak hazırlandı. Yarıiletkenin diğer yüzüne ise Gümüş metali buharlaştırıldı ve Schottky kontak hazırlandı. Elde edilen Ag/GaP/Al kontağının I-V ve C-V ölçümleri incelendi. I-V ve C-V grafikleri çizildi. Bu grafikler yardımı ile Schottky Diyotunun idealite faktörü (n), engel yüksekliği ( ? B), seri direnci (RS) ve boşluk yoğunluğu (Nd) hesaplandı.Anahtar kelimeler: Yarıiletken, Yasak enerji aralığı, Optik özellikler, Schottky diyot.

Preporation of GaP/Metal Schottky Diode and İnvestigation of Electronic PropertiesIn this study, optical and electrical properties of Gallium Phosphide (GaP) thin film prepared by Liquid-encapsulated Czochralski (LEC) technique were investigated. The optical properties of the sample were investigated by obtain absorption and transmittance measurements. In this measurements GaP thin film band gap was obtained as 2,24 eV. The change of refractive index- wavelength and oscillator energy were investigated. Later, on one surface of semiconductor layer was prepared with Al coating and ohmic contact was prepared. The other surface of semiconductor was prepared by evaporated silver metal and Schottky contact was prepared. I-V and C-V measurements of the Ag/GaP/Al contact were investigated. I-V and C-V diagrams were drown. Schottky Diode?s ideality factor (n), barrier height ( ? B), series resistance (RS) and donor concentration (Nd) were calculated.Key Words: Semiconductor, band gap, optical properties, Schottky diode.
Preporation of GaP/metal Schottky diode and investigation of electronic properties
Keywords: Fizik ve Fizik Mühendisliği